Penerapan Algoritma K-Means Untuk Clustering Big Five Personality - Patrick Lay; Ary Budi Warsito (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Personality is the combination of characteristics or qualities that form an individual’s distinctive character. Every individual on earth has different personalities depending on their biological and environmental factors. To find out about one’s personality, we can take a personality test which is a tool or method used to assess human personality. One of the most popular approaches to personality nowadays is the Big Five theory of personality, where this theory suggests that human personality is composed of five basic traits: Openness, Conscientiousness, Extroversion, Agreeableness and Neuroticism. While doing research, we found how some people tend not to have knowledge about their personality types. Therefore, we started this research with the aim of determining the user's personality, strengths and weaknesses of their personality in order to help them develop and improve themselves. This research used the PCA method and K-Means algorithm to aid in the clustering process.